La contribució de Carles Salvador al «teatre valencià» - Rosselló, Ramon X. (Caplletra. Revista Internacional de Filologia, 2015)
From 1915 to the postwar years, Caries Salvador wrote over a dozen plays, some of which were left unpublished, and others which were never brought to the stage. Comedies, comic interludes and a miracle story about Saint Vicent make up this group of texts. Roselló analyzes them in detail.